On the Authenticity of Two Presumed Paleolithic Female Figurines from the Art Market - Sibylle Wolf; Rainer-Maria Weiss; Patrick Schmidt; Flavia Venditti (Heritage)
In March 2022, an auction house in Zurich sold two female figurines made from mammoth ivory, along with other prehistoric artefacts. This is a rare occurrence because the scarcity and value of Paleolithic figurines have limited their presence in the international art market. Researchers from the Archaeological Museum Hamburg and the University of Tübingen subsequently undertook in situ and non-destructive investigations to illuminate the authenticity of the two figurines. We conducted a comprehensive analytical study that included detailed microscopic optical observations and spectroscopic investigations. This methodological approach, combined with a thorough comparison to contemporary ivory figurine replicas, proved effective and clearly demonstrated that the specimens were forgeries. Research efforts of this kind are crucial, as they significantly help reduce the spread of intentional fakes posing as genuine artefacts in the art market. By doing so, we foster collaboration between academic institutions and the art market to preserve and protect the integrity and value of authentic archaeological and cultural heritage.